Proses Siswa SMP Feminin dan Maskulin dalam Memahami Bentuk Aljabar - Putu Windayanti; Siti Khabibah; Budi Rahadjeng (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The aim of the study is to describe students’ procesess on understanding algebraic expression. This research was descriptive study with qualitative approach. Two students with the higher rank in mathematics’ test were selected as the research subject. The data were collected by giving algebraic forms problem based on Anderson’s cognitive processes of understand and interviews. The results shows that on: interpreting, feminin & masculine student transforms the given information into variables to determine the algebraic forms of the problem, the difference is the letters that used to represent variables; exemplying, both student gives appropriate specific examples, the difference is masculine student gives examples of algebraic forms which terms contain single variable; classifying, both student classifies the algebraic forms that has three terms and explains why an algebraic form called as three-terms of algebraic form; inferring, both student use the information in the problem to conclude the solution; summarizing, both student generalize the general form of three-variables of algebraic form; comparing, feminin student compare the simmiliarities to determine algebraic forms that have the same characteristics as the algebraic form given, while masculline student can not find the simmiliarities. It causes a bias in masculline student on exemplying.